THE ANALYSIS OF SISKEUDES (SISTEM KEUANGAN DESA – VILLAGE FINANCIAL INFORMATION SYSTEM) IMPLEMENTATION USING INFORMATION SYSTEM SUCCESS MODEL FROM DELONE AND MCLEAN IN MAJALENGKA REGENCY - Amalia, Rizki; Adrianto, Zaldy (Sosiohumaniora, 2020)
This researchwas conducted to determine the success level of the implementation of Siskeudes (Sistem Keuangan Desa ? Village Financial Information System) by using the updated DeLone and McLean information system success model that had been adjusted to the implementation of Siskeudes as a mandatory information system in Villages in Majalengka Regency, West Java. This research examined the impact of quality of system,quality ofinformation, and service quality on user satisfaction, and the impact of user satisfaction on perceived net benefit. Data wereobtained from questionnaires distributed to 65 respondents in Majalengka Regency. The methods used in this study was descriptive analysis with path analysis, while for hypothesestesting, the t test was performed and also the p-value test. The results of this study indicated a significant effect of system quality and the quality of service on user satisfaction, and also the effect of user satisfaction on perceived net benefits, but showed no significant effects of the quality of information on user satisfaction.